Duration and Success of Nerve Rehabilitation after Elbow Injuries in Children - Murtezani, Ardiana; Abazi, Nerimane; Sllamniku, Sabit; Rrecaj-Malaj, Shkurta; Kepuska, Arbnora B. (Journal of Pediatric Neurology, 2020)
Neurological complications after the supracondylar humerus fractures with a displacement of fragments result from traction, direct trauma, or nerve ischemia. The beginning of early rehabilitation, from when the arm is still immobilized, leads to complete restoration of the elbow joint, and thus any delay in starting the rehabilitation will have consequences, ranging from lighter ones to full disability. This study analyzed the impact of injured nerves, length of immobilization, and interruptions during rehabilitation on the rehabilitation duration (RD). A sample of 140 children of both genders with post-traumatic elbow injuries was considered, from the birth to 15 years. The sample was collected in cooperation with an orthopedist, pediatrician, and physiotherapist. The diagnosis was confirmed by physical and neurological examination and by radiography. The type of injury affects the RD. The supracondylar humerus fracture has a longer RD, with the average 85.45 days. We conducted the linear correlation test, between cases with injured nerves and cases without in relation to RD. The analysis provided significant statistical data (p < 0.01) proving that injured nerves are an important factor in RD. Of cases with radius nerve injury, 62.5% achieved full recovery. The analysis shows that for p < 0.01 (for cases in general) the immobilization duration has a significant impact on RD. Among patients who had no interruptions of rehabilitation, 92 achieved an excellent rehabilitation success, with an average number of 29.7 procedures and an average RD of 56 days. Injured nerves proved to have a great impact on the RD for elbow injuries, while not showing any impact on the rehabilitation success. Interruptions of rehabilitation treatments proved to have a statistical significance, meaning they have a high impact on the RD and success.
Keywords: nerve injury; supracondylar fractures; rehabilitation; children